(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Financial markets, services, and institutions are undergoing profound transformations as a result of legislative reforms and technology advancements that have arisen since the Global Financial Crisis of 2008. RegTech, short for regulatory technology, is the intersection of these two trends, and it refers to the use of technology, typically information technology, to the tasks of monitoring, reporting, and complying with regulations. To keep up with the times, regulators in developing markets have started to rethink their approaches to regulation and embrace a more data- and technology-based strategy. New forms of cooperation between regulators and technology entrepreneurs will be necessary to bring about the future of a RegTech approach to regulation, which is only now beginning to become visible. While it’s true that RegTech isn’t a magic bullet, when coupled with astute decision making, it may put regulators in a far stronger position to meet the challenges in the financial sector.